Analysis of risk factors for the development of obesity in preschool children: a logistic model analysis - Jin, Huasheng; Zhou, Huihui; Chen, Kai (Frontiers in Pediatrics, 2025)
IntroductionObesity, characterized by abnormal fat accumulation, has become a significant global health concern. The prevalence of obesity in preschool children is rising across regions, highlighting the need for a thorough analysis of risk factors and effective interventions to address this growing epidemic. The aim of this study was to identify and analyze the main risk factors for the development of obesity in preschool children and explore effective interventions.MethodsWe collected clinical data from 910 preschool children who underwent a physical examination at our hospital from January 2023 to December 2023. Based on specific inclusion and exclusion criteria, we categorized the children into two groups: the obesity group (149 cases) and the non-obesity group (761 cases). Using univariate analysis and logistic regression modeling, we identified risk factors associated with obesity development.ResultsOut of the 910 children, 149 were diagnosed as obese, representing 16.37% of the total. High birth weight, high parental body mass index (BMI), picky eating habits, preference for meat, frequent consumption of junk food, and binge eating were found to be significant risk factors for obesity in preschool children. Meanwhile, higher parental education levels and longer daily outdoor activity times were considered protective factors against obesity.DiscussionEffective interventions targeting the above risk factors are necessary to minimize the incidence of obesity and promote the healthy development of children.